Prospective Elementary Science Teacher in Developing Lesson Plan through Integration of STEM-Based TPACK - Purnama Sari, Winda; Rahmawati Mega, Iful (FKIP Universitas Lampung, 2022)
This study aims to determine the effect of STEM-integrated TPACK on the ability to plan science lessons and explore the ability of student learning planning in developing self competencies to become adaptive, professional, creative, and innovative. The research method was a survey with a quantitative approach with 34 even-semester students at the Department of elementary teacher education for the 2021/2022 academic year. Data collection used a questionnaire with a Likert scale and documentation. Data analysis techniques used SEM through AMOS and descriptive analysis. The results show that students are able to implement STEM-integrated TPACK within the 51-75 rating range. The designed model has been fit through GOF and GOFI values. TPK, CK and PK had a direct effect on STEM skills significantly for student’s abilities in preparing lesson plans. Indirect effect to show that the ability of STEM-integrated TPK, PCK, CK, TK, TPACK, PK has an indirect impact on students' ability to plan science lessons.Keywords: lesson plan, TPACK, STEM, prospective science teacher.DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1620-1634